South African History textbook research – a review of the scholarly literature (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
School history textbooks are seen to embody ideological messages about whose history is important, as they aim both to develop an ‘ideal’ citizen and teach the subject of history. Since the 1940s, when the first study was done, there have been studies of South African history textbooks that have analysed different aspects of textbooks. These studies often happen at a time of political change (for example, after South Africa became a republic in 1961 or post-apartheid) which often coincides with a time of curriculum change. This article provides an overview of all the studies of South African history textbooks since the 1940s. We compiled a data base of all studies conducted on history textbooks, including post graduate dissertations, published journal articles, books and book chapters. This article firstly provides a broad overview of all the peer-reviewed studies, noting in particular how the number of studies has increased since 2000. The second section then engages in a more detailed analysis of the studies that did content analysis of textbooks. We compare how each study has engaged with the following issues: the object of study, the methodological approach, the sample of textbooks and the theoretical or philosophical orientation. The aim is to provide a broad picture of the state of textbook analysis studies over the past 75 years, and to build up a database of these studies so as to provide an overview of the nature of history textbook research in South Africa.
Keywords: History textbooks; School history; South Africa; Scholarly literature